2011
DOI: 10.1002/jssc.201100720
|View full text |Cite
|
Sign up to set email alerts
|

pH‐based cation exchange chromatography in the capture and elution of monoclonal antibodies

Abstract: Cation exchange chromatography separates adsorbed proteins by controlling the salt concentration or the mobile phase pH. This study examines the pH-based method for binding and elution of monoclonal antibodies (MAbs). Five different clones with isoelectric points from 6 to 9 were evaluated. We performed our studies using a new chromatography resin (Nuvia™ S), which has high binding capacity. A three-column process incorporating Nuvia S as a capture step was also demonstrated for the purification of MAb from ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…IEX is the preferred technique for preparative and process scale separation for charge variants. While bench‐top analytical scale resolution has improved tremendously (Amand et al, ; Farnan & Moreno, ; Fekete et al, , ; Follman & Fahrner, ; Joshi, Kumar, & Rathore, ; Kang, Kutzko, Hayes, & Frey, ; Lingg et al, ; Ng & Snyder, ; Nordborg et al, ; Rea, Moreno, Lou, & Farnan, ; Santora, Kaymakcalan, Sakorafas, Krull, & Grant, ; Talebi et al, ; Talebi, Shellie, Hilder, Lacher, & Haddad, ; Tao, Carta, Ferreira, & Robbins, , ; Tao, Perez, Carta, Ferreira, & Robbins, ; Weitzhandler et al, ; Zhang, Patapoff, Farnan, & Zhang, ), industrial separation of charge variants remains challenging due to the scale and capacity required. For most industrial processes, the stationary phase, physical parameters of the columns, are already fixed.…”
Section: Separation and Purification Of Charge Variants In Downstreammentioning
confidence: 99%
“…IEX is the preferred technique for preparative and process scale separation for charge variants. While bench‐top analytical scale resolution has improved tremendously (Amand et al, ; Farnan & Moreno, ; Fekete et al, , ; Follman & Fahrner, ; Joshi, Kumar, & Rathore, ; Kang, Kutzko, Hayes, & Frey, ; Lingg et al, ; Ng & Snyder, ; Nordborg et al, ; Rea, Moreno, Lou, & Farnan, ; Santora, Kaymakcalan, Sakorafas, Krull, & Grant, ; Talebi et al, ; Talebi, Shellie, Hilder, Lacher, & Haddad, ; Tao, Carta, Ferreira, & Robbins, , ; Tao, Perez, Carta, Ferreira, & Robbins, ; Weitzhandler et al, ; Zhang, Patapoff, Farnan, & Zhang, ), industrial separation of charge variants remains challenging due to the scale and capacity required. For most industrial processes, the stationary phase, physical parameters of the columns, are already fixed.…”
Section: Separation and Purification Of Charge Variants In Downstreammentioning
confidence: 99%
“…Abbreviations: ATPS, aqueous two-phase system; ATPE, aqueous two-phase extraction; CHO, Chinese hamster ovary; HPS, hydroxypropyl starch; IgG, immunoglobulin G; mAb, monoclonal antibody; VR, volume ratio regeneration, ligand leaching, and antibody aggregation at low pH elution conditions [6]. Recently, a variety of alternative techniques have been developed to improve the process efficiency and economics of antibody production, including mixed-mode adsorption [7], membrane adsorption [8], cationexchange chromatography [6], fluoroapatite chromatography [9], and aqueous two-phase extraction (ATPE).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variety of alternative techniques have been developed to improve the process efficiency and economics of antibody production, including mixed-mode adsorption [7], membrane adsorption [8], cationexchange chromatography [6], fluoroapatite chromatography [9], and aqueous two-phase extraction (ATPE).…”
Section: Introductionmentioning
confidence: 99%
“…These include low‐binding capacity, high cost, lack of an effective cleaning procedure, or short lifetime. Nonaffinity capture methods (e.g., ion exchange and mixed mode) have been evaluated in several studies and separation of HCPs is often found to be challenging because of the nonspecific nature of these separation techniques . Therefore, an in‐depth understanding of the HCP chromatographic behavior would provide valuable insight for the rational design of purification processes …”
Section: Introductionmentioning
confidence: 99%
“…Nonaffinity capture methods (e.g., ion exchange and mixed mode) have been evaluated in several studies and separation of HCPs is often found to be challenging because of the nonspecific nature of these separation techniques. [14][15][16][17] Therefore, an in-depth understanding of the HCP chromatographic behavior would provide valuable insight for the rational design of purification processes. 18 Besides the immunogenicity concern, HCPs can also compromise product quality and shelf-life by resulting in degradation of protein or excipient, which leads to fragmentation, aggregation, and particle formation.…”
Section: Introductionmentioning
confidence: 99%